Rootstock effect on yield, initial fruit quality, and lycopene content of ‘Tasti Lee’ tomatoes - Tricia Jenkins; Cary Rivard; Eleni Pliakoni (Urban Food Systems Symposium, 2020)
Tomatoes are a high-value crop commonly grown in high tunnel systems in the central United States. Grafting is an important tool for mitigation of soil borne disease pressure and abiotic stresses in tomato production and is used world-wide in protected growing systems such as high tunnels. ‘Tasti Lee’ is a high-quality tomato cultivar that is grown in the southeastern U.S. and has been bred for superior fresh-eating quality and enhanced lycopene content. Previous high tunnel trials in Kansas have shown that ‘Tasti-Lee’ significantly increases marketable yields when grafted to the vigorous rootstock ‘Maxifort.’ The objective of this trial was to investigate the yield and potential fruit quality impacts of ‘Tasti-Lee’ when grafting to five different roostocks and grown in a central U.S. high tunnel with little disease pressure. Due to the diverse impacts of grafting on fruit quality found in the literature, it is important to conduct localized rootstock trials and make conclusions on specific rootstock/scion combinations. ‘Tasti Lee’ tomatoes were grafted to ‘Maxifort,’ ‘DRO 141 TX,’ ‘Fortamino,’ ‘Estamino,’and ‘RST-04-106’ rootstocks and grown in a high tunnel system in Kansas in 2019. The experiment was arranged in a randomized complete block design. Total yield, marketable yield, and fruit size were assessed for the whole season on a per plant basis. Red ripe tomato fruit were used for assessing soluble solids content (SSC), titratable acidity (TA), lycopene content, and ascorbic acid content. Although the results were not statistically significant, all rootstocks increased the marketable fruit number and fruit size over the non-grafted control. ‘Maxifort, ‘Fortamino,’ and ‘Estamino’ were the best performing rootstocks. No differences in SSC, TA, lycopene content, or ascorbic acid were found due to grafting. Our results indicate that ‘Tasti-Lee’ could be a successful candidate for high-tunnel grafting systems in the central U.S.
Keywords: Solanum lycopersicum; scion; soluble solids; carotenoids; ascorbic acid; grafting; fruit weight